AMSER Guide to Applying for Radiology Residency - Sravanthi Reddy; Janet Neutze; William Randazzo; Petra Lewis (Association of American Medical Colleges, 2011)
Abstract This guide helps answer frequently asked questions about how to apply to radiology residency. This guide includes sections on helping a student figure out if radiology is right for him/her, what makes a successful candidate, the time line of suggestions of what to do starting from the first year of medical school to be a successful candidate, and what radiology residency programs are looking for. It also describing the application and interview process, and lists resources that may be helpful to the process. The guide has been disseminated to the Alliance of Medical Student Educators in Radiology members and has received positive feedback.